Sealing Capability and SEM Observation of the Implant-Abutment Interface - Fabio C. Lorenzoni; Paulo G. Coelho; Gerson Bonfante; Ricardo M. Carvalho; Nelson R. F. A. Silva; Marcelo Suzuki; Thelma Lopes Silva; Estevam A. Bonfante (Hindawi Limited, 2011)
To evaluate the sealing capability of external hexagon implant systems and assess the marginal fit, two groups (𝑛=10 each) were employed: SIN (Sistema de Implantes Nacional, Brazil) and Osseotite, (Biomet 3i, USA). Sealing capability was determined by placing 0.7 𝜇L of 1% acid-red solution in the implant wells before the torque of their respective abutments. Specimens were then placed into 2.5 mL vials filled with 1.3 mL of distilled water with the implant-abutment interface submerged. Three samples of 100 𝜇L water were collected at previously determinate times. The absorbance was measured with a spectrophotometer, and the data were analyzed by Two-way ANOVA (𝑃<.05) and Tukey's test. Marginal fit was determined using SEM. Leakage was observed for both groups at all times and was significantly higher at 144 hrs. SEM analysis depicted gaps in the implant-abutment interface of both groups. Gaps in the implant-abutment interface were observed along with leakage increased at the 144 hrs evaluation period.